SOSIALISASI HARGA ECERAN OBAT TERTINGGI (HET) OBAT - Neneng Sri Purwaningsih; Syaiful BahriI; Dhifan Arrahman K (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
In order to meet the public's need for medicines and ensure access to medicines for the entire community, the government issued a generic medicine pricing policy. The consumer protection law regulates how consumers have the right to obtain information about a product to be consumed, as well as consumers of medicinal products. Information in the form of the Highest Retail Price (HET), the ingredients contained in the drug, the efficacy of the drug, the side effects of the drug, and the authenticity of a drug is a consumer's human right. The aim of this community service activity is to provide public knowledge regarding the Highest Retail Price (HET) of drugs so that the public as consumers are protected from business actors who sell drugs above the Highest Retail Price (HET) for drugs and the public has clear access to information about a drug. The activities carried out are in the form of direct outreach or counseling to the community. The preparatory activities carried out included preparation of the socialization venue, coordination meetings, preparation, implementation and evaluation of activities. The location of this activity was at Kp. Gulusur RT 01 RW 08, Gunung Sindur District, Bogor Regency, West Java, attended by 59 participants, consisting of lecturers, students and Public. From the results of implementing this community service activity, the public knows the Retail Price of Medicines (HET) and understands the applicable regulations regarding this matter. The response of the local community to the community service activities that we carry out is very enthusiastic. In general, in socializing the importance of the public knowing the highest retail price of a drug.